Hidden faces, altered perceptions: the impact of face masks on interpersonal perception - Wang, Shuai; Han, Chengyang; Sang, Zihan; Zhang, Xuhui; Chen, Shitao; Wang, Haoran; Wang, Gang; Xu, Yiqian; Lei, Xue; Chen, Jixu (Frontiers in Psychology, 2023)
The pandemic has made wearing masks commonplace, prompting researchers to investigate their effects on interpersonal perception. Findings indicate masks obstruct face identification and expression recognition, with lower face cues being most affected. When judging attractiveness, masks can enhance the appeal of less attractive faces, but reduce the appeal of more attractive faces. Trust and speech perception outcomes are inconclusive. Future studies could focus on individual differences in how masks influence our perception of others.